The world's master paintings from the early Renaissance to the Present Day: Vol.2 - Christopher Wright (1945- (Routledge, 1992)
The book lists in alphabetical order all the locations, together with the names of the painters represented in the collections, and the numbers of their paintings. Each location entry is prefaced by a short description of the general scope of the collection and, where relevant or available, a general bibliography